Assessment of Digital Solutions for Conformity Assessment of Legally Controlled Measuring Instruments in Tanzania - Nyoni, Faraja (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The advent of state-of-the-art digital technologies since 2011 has led to the digital transformation of legal metrology practices to ensure the trustworthiness of software-controlled measuring instruments globally. Despite the digital transformation in legal metrological practices, the conformity assessment of legally controlled measuring instruments is manually done (i.e., paper-based) in Tanzania. The paper-based conformity assessment of legally controlled measuring instruments is prone to error and lacks efficiency and effectiveness. This study aimed to assess digital solutions for improving conformity assessment through a comprehensive survey conducted across various regions in Tanzania, targeting a stratified sample of 51 respondents from organizations involved in legal metrology. Data was collected using structured questionnaires. SPSS® 23.0 analyzed the collected data. The reliability testing through the Cronbach’s alpha value was 0.887, implying high internal consistency of the data collected. The findings revealed that the awareness level spans from neither aware to fully aware. The overall readiness level was as follows: digital solutions (level 2), instrument (level 3), infrastructure (level 3), skilled personnel (level 2), financial arrangement (level 2) and government policy (level 4). The overall readiness level approximated to level 4. Thus, the findings indicate that there is an intermediate level of readiness to adapt state-of-the-art technologies to enhance conformity assessment of legally controlled measuring instruments. Approximately 75% of respondents are aware of various digital solutions for conformity assessment of legally controlled measuring instruments, including digital conformity assessment certificates, digital twins for products and instruments, and smart sensors.